Type 2 Diabetes Mellitus and Latent Tuberculosis Infection Moderately Influence Innate Lymphoid Cell Immune Responses in Uganda - Ssekamatte, Phillip; Nakibuule, Marjorie; Nabatanzi, Rose; Egesa, Moses; Musubika, Carol; Bbuye, Mudarshiru; Hepworth, Matthew R.; Doherty, Derek G.; Cose, Stephen; Biraro, Irene Andia (Frontiers in Immunology, 2021)
Background: Type 2 diabetes mellitus (T2DM) is a major risk factor for the acquisition of latent tuberculosis (TB) infection (LTBI) and development of active tuberculosis (ATB), although the immunological basis for this susceptibility remains poorly characterised. Innate lymphoid cells (ILCs) immune responses to TB infection in T2DM comorbidity is anticipated to be reduced. We compared ILC responses (frequency and cytokine production) among adult patients with LTBI and T2DM to patients (13) with LTBI only (14), T2DM only (10) and healthy controls (11). Methods: Using flow cytometry, ILC phenotypes were categorised based on (Lin−CD127+CD161+) markers into three types: ILC1 (Lin−CD127+CD161+CRTH2-CD117−); ILC2 (Lin−CD127+CD161+CRTH2+) and ILC3 (Lin−CD127+CD161+CRTH2−NKp44+/−CD117+). ILC responses were determined using cytokine production by measuring percentage expression of interferon-gamma (IFN-γ) for ILC1, interleukin (IL)-13 for ILC2, and IL-22 for ILC3. Glycaemic control among T2DM patients was measured using glycated haemoglobin (HbA1c) levels. Data were analysed using FlowJo version 10.7.1, and GraphPad Prism version 8.3. Results: Compared to healthy controls, patients with LTBI and T2DM had reduced frequencies of ILC2 and ILC3 respectively (median (IQR): 0.01 (0.005-0.04) and 0.002 (IQR; 0.002-0.007) and not ILC1 (0.04 (0.02-0.09) as expected. They also had increased production of IFN-γ (median (IQR): 17.1 (5.6-24.9)), but decreased production of IL-13 (19.6 (12.3-35.1)). We however found that patients with T2DM had lower ILC cytokine responses in general but more marked for IL-22 production (median (IQR): IFN-γ 9.3 (4.8-22.6); IL-13 22.2 (14.7-39.7); IL-22 0.7 (IQR; 0.1-2.1) p-value 0.02), which highlights the immune suppression status of T2DM. We also found that poor glycaemic control altered ILC immune responses. Conclusion: This study demonstrates that LTBI and T2DM, and T2DM were associated with slight alterations of ILC immune responses. Poor T2DM control also slightly altered these ILC immune responses. Further studies are required to assess if these responses recover after treatment of either TB or T2DM.